Interface controlled micro- and macro- mechanical properties of aluminosilicate fiber reinforced SiC matrix composites. Issue 3 (March 2017) - Liu, H.T.; Yang, L.W.; Han, S.; Cheng, H.F.; Mao, W.G.; Molina-Aldareguía, J.M.
Abstract: Novel Nextel™ 440 aluminosilicate fiber reinforced SiC matrix composites, with/without chemical vapor deposited carbon interphase were fabricated by polymer derived ceramic process, and they were studied by a combination of micro- and macro- mechanical techniques such as nanoindentation, micropillar splitting, fiber push-in, digital image correction and high temperature three point bend tests. Specifically, micropillar splitting test was firstly employed to measure in-situ the localized fracture toughness. The results revealed that the carbon interphase can effectively hinder the interfacial reactions between Nextel™ 440 fiber and SiC matrix, thus remarkably weakening the composite interfacial shear strength from ∼293 MPa to ∼42 MPa, and enhance the composite fracture toughness from ∼1.8 MPa√m to ∼6.3 MPa√m, respectively. This is mainly a consequence of weak interface that triggers crack deflection at the fiber/interphase interface. Finally, this novel composite showed stable mechanical properties in vacuum at temperature range from 25 °C to 1000 °C.